Three-dimensional CFD modeling of transport phenomena in multi-channel anode-supported planar SOFCs. (May 2015) - Zhang, Zhonggang; Yue, Danting; Yang, Guogang; Chen, Jingfeng; Zheng, Yifeng; Miao, He; Wang, Weiguo; Yuan, Jinliang; Huang, Naibao
Abstract: In this study, a three-dimensional computational fluid dynamics (CFD) model is developed and applied for anode-supported planar SOFC involving multi-channels. The developed model is first validated in agreement with the experimental data obtained at same conditions. Three different flow arrangements (co-, counter- and cross-flow) are simulated and compared in terms of cell overall performance and various transport phenomena occurred inside the SOFC single cell functional components. Local distribution of temperature, mass flow rate, current density, gas concentrations of reactants and products in both fuel and air sides under different flow arrangements is predicted and presented. It is found that the co-flow and counter-flow arrangements have a better performance than that of the cross-flow arrangement at the same operating conditions. It is also found that the temperature for the three flow arrangements is unevenly distributed and the significant temperature gradients exist along the length of the cell. The mass flow rate of fuel at the inlet of each channel is uniform, however its difference between the side channel and the channel at the center is increasing along the fuel flow direction, which reaches a maximum value at the outlet region. It is also predicted that the maximum current density is located at the interfaces between the channels, ribs and the electrodes resulting in a large over-potential and a heat source in the electrodes, which is harmful to the cell overall performance and working life time.